Stock Prices, Real Exchange Rates, and Optimal Capital Accumulation. (IMF Working Papers; Working Paper, 1988)
This paper analyzes the dynamics of the real exchange rate and the price of equity for a small open economy using an optimizing model in which the process of capital accumulation entails adjustment costs. The analysis demonstrates that along an adjustment path toward long-run equilibrium, appreciation of the real exchange rate will accompany a decline in the market price of equity, whereas depreciation of the real exchange rate will accompany a rise in the price of equity. This relationship results from the requirement that non-traded inputs are used in the investment process. In the short-run, though, the effects on these variables depend critically on whether disturbances originate in the non-traded sector and on whether disturbances are perceived as temporary or permanent. The disturbances considered include changes in fiscal policies as well as changes in the world interest rate.